Advances in research and application of artificial intelligence and radiomic predictive models based on intracranial aneurysm images - Wen, Zhongjian; Wang, Yiren; Zhong, Yuxin; Hu, Yiheng; Yang, Cheng; Peng, Yan; Zhan, Xiang; Zhou, Ping; Zeng, Zhen (Frontiers in Neurology, 2024)
Intracranial aneurysm is a high-risk disease, with imaging playing a crucial role in their diagnosis and treatment. The rapid advancement of artificial intelligence in imaging technology holds promise for the development of AI-based radiomics predictive models. These models could potentially enable the automatic detection and diagnosis of intracranial aneurysms, assess their status, and predict outcomes, thereby assisting in the creation of personalized treatment plans. In addition, these techniques could improve diagnostic efficiency for physicians and patient prognoses. This article aims to review the progress of artificial intelligence radiomics in the study of intracranial aneurysms, addressing the challenges faced and future prospects, in hopes of introducing new ideas for the precise diagnosis and treatment of intracranial aneurysms.